Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with 2019 Novel Coronavirus (SARS-CoV-2) Infection - Helen Kest; Ashlesha Kaushik; William DeBruin; Mario Colletti; David Goldberg (Case Reports in Pediatrics)
We report three critically ill pediatric patients (aged 6–10 years), presenting with features of multisystem inflammatory syndrome in children (MIS-C) from April 4 to May 10, 2020, to a tertiary-care center in New Jersey, United States. All patients tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and were previously healthy. Clinical presentations were similar with fever, abdominal pain, gastrointestinal complaints, and/or rash. One patient had altered mental status with cerebrospinal fluid (CSF) findings consistent with aseptic meningitis. Laboratory values were remarkable for high levels of C-reactive protein, D-dimers, B-type natriuretic peptide (BNP), and troponin in all patients. All had low albumin levels. Evaluation for other infectious etiologies was negative. All of the patients were critically ill, requiring admission to the intensive care unit. All had circulatory shock and needed inotropes. Two patients had respiratory failure requiring advanced respiratory support and one had cardiac dysfunction. All patients received steroids, and two received intravenous immunoglobulin (IVIG). One patient received tocilizumab. None of the children died. MIS-C is a recently recognized pediatric illness spectrum in association with SARS-CoV-2 infection, and clinical characterization is essential for understanding disease mechanisms to inform clinical practice.